2004
DOI: 10.1345/aph.1e204
|View full text |Cite
|
Sign up to set email alerts
|

Population-Based Medication Reviews: A Descriptive Analysis of the Medication Issues Identified in a Medicare Not-for-Profit Prescription Discount Program

Abstract: Iowa Priority Brown Bag Medication Reviews showed that individuals with fair/poor health, higher numbers of medications, and more chronic conditions were likely to have medication issues. Reviews generated discussions between physicians and patients, produced some medication changes, and helped individuals save money.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
27
0

Year Published

2007
2007
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(27 citation statements)
references
References 18 publications
(11 reference statements)
0
27
0
Order By: Relevance
“…A number of studies have demonstrated that the elderly are at a greater risk of experiencing drug-related problems (DRPs) compared to the remainder of the population [2][3][4]. This is due to numerous factors, including changes in pharmacodynamics and pharmacokinetics, a higher incidence of multiple chronic diseases, polypharmacy and reduced cognitive capacity.…”
mentioning
confidence: 99%
“…A number of studies have demonstrated that the elderly are at a greater risk of experiencing drug-related problems (DRPs) compared to the remainder of the population [2][3][4]. This is due to numerous factors, including changes in pharmacodynamics and pharmacokinetics, a higher incidence of multiple chronic diseases, polypharmacy and reduced cognitive capacity.…”
mentioning
confidence: 99%
“…This finding could be the result of patients’ approaching the pharmacist for another MCA after a positive prior experience. In a US study 24 % of individuals who had received a medication review (brown bag review) responded positively when asked if they would have a review annually [28]. In addition, from a pharmacist’s perspective, experienced MCA users may be easy to identify through the pharmacy’s patient profile system, and engage since they have responded positively to MCA in the past.…”
Section: Discussionmentioning
confidence: 99%
“…A recent study 15 found that this approach is cost-effective, promoting changes in medication regimen and encouraging pharmacist/ physician dialogue. The medication review can be viewed as an enhanced service that is commissioned by each primary care organization.…”
mentioning
confidence: 99%